Retinoic Acid Potentiates the Therapeutic Efficiency of Bone Marrow-Derived Mesenchymal Stem Cells (BM-MSCs) against Cisplatin-Induced Hepatotoxicity in Rats - Maha M. Azzam; Abdelaziz M. Hussein; Basma H. Marghani; Nashwa M. Barakat; Mohsen M. M. Khedr; Nabil Abu Heakel (MDPI AG, 2022)
(1) Background: Hepatotoxicity is a common health problem, and oxidative stress plays a crucial role in its underlying mechanisms. We inspected the possible effect of retinoic acid (RA) in the potentiation of hepatoprotective effect of bone marrow mesenchymal stem cells (BM-MSCs) against Cisplatin (Cis)-induced hepatotoxicity. (2) Methods: 60 male Sprague Dawley rats (SD) were separated randomly and designated to six main equal groups as follows: (1) Control group, (2) Cis group (rats got Cis 7 mg/Kg i.p.), (3) Cis + vehicle group (as group 2, but rats received the (vehicle) culture media of BM-MSCs), (4) Cis as in group 2 + BM-MSCs (1x106), (5) Cis as for group 2 + RA 1 mg/Kg i.p., and (6) Cis and BM-MSCs as for group 3 + RA as for group 4. Liver injury was assessed by measuring liver enzymes (ALT, AST), while liver toxicity was evaluated by histopathological examination. Apoptotic marker caspase-3 protein was detected immunohistochemically. Real time PCR was performed to detect NADPH oxidase and TNF-α at transcription levels. Oxidative stress was investigated by colorimetric measurement of MDA, GSH and catalase. (3) Results: Contrary to the Cis group (p < 0.05), BM-MSCs/RA supplementation resulted in a substantial decrease in serum levels of hepatic impairment indicators such as ALT, AST and oxidative stress markers such as MDA, as well as an increase in hepatic GSH, Catalase, and a decrease in expression of TNF-α and downregulation of NADPH oxidase. The improvement after therapy with BM-MSCs/RA was confirmed by histopathological examination. Moreover, the downregulation of caspase-3 in liver tissue after BM-MSCs/RA treatment was validated by immunohistochemistry investigation. (4) Conclusions: BM-MSCs and RA attenuated Cis induced hepatotoxicity through downregulation of oxidative stress resulted in modulation of anti-inflammatory TNF-α and apoptosis caspase-3 indicating a promising role in hepatotoxicity.